2014
DOI: 10.1016/j.breast.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Sexual functioning in women after mastectomy versus breast conserving therapy for early-stage breast cancer: A prospective controlled study

Abstract: Although little differences were seen in sexual functioning in the BCT group during prospective analyses and in comparison with healthy controls, analyses revealed that women who underwent a ME were at risk for post-operative sexual dysfunctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 46 publications
6
87
1
5
Order By: Relevance
“…Women with lumpectomy present fewer dysfunctions that those who have a unilateral mastectomy or a bilateral mastectomy [6, 9, 26, 27]. Women without breast reconstruction have the greatest probability of sexual dysfunction [28].…”
Section: Discussionmentioning
confidence: 99%
“…Women with lumpectomy present fewer dysfunctions that those who have a unilateral mastectomy or a bilateral mastectomy [6, 9, 26, 27]. Women without breast reconstruction have the greatest probability of sexual dysfunction [28].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Aerts et al 23 reported that women conservative surgery post feature countless negative emotions, such as depression and anxiety, concerns about recurrences of the disease, change in femininity and decreased sexual attraction.…”
Section: Discussionmentioning
confidence: 99%
“…107 Both premenopausal and postmenopausal BRCA carriers undergoing RRSO compared with screening have been shown to have decreased pleasure and satisfaction and increased dyspareunia. Beyond the physical changes in sensation and vaginal dryness, women can have altered body images and difficulty with desire and arousal.…”
Section: Reproduction and Sexualitymentioning
confidence: 99%